2003
DOI: 10.1091/mbc.e02-12-0784
|View full text |Cite
|
Sign up to set email alerts
|

EIF3 p170, a Mediator of Mimosine Effect on Protein Synthesis and Cell Cycle Progression

Abstract: l-Mimosine, a plant amino acid, can reversibly block mammalian cells at late G1 phase and has been suggested to affect translation of mRNAs such as p27, the CDK inhibitor. However, the mechanism of this effect is not known. Regulation of translation generally occurs at the initiation step that, in mammalian cells, is a complex process that requires multiple eukaryotic initiation factors (eIFs) and ribosome. The effects of mimosine on initiation factors or regulators consequently will influence translation init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
114
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(130 citation statements)
references
References 52 publications
16
114
0
Order By: Relevance
“…RNA Extraction and Ribonuclease Protection Assay-Total RNA was extracted using the RNeasy minikit (Qiagen) as described previously (10). Nuclear RNAs were prepared by first isolating nuclei as described previously (16,17).…”
Section: For [mentioning
confidence: 99%
See 2 more Smart Citations
“…RNA Extraction and Ribonuclease Protection Assay-Total RNA was extracted using the RNeasy minikit (Qiagen) as described previously (10). Nuclear RNAs were prepared by first isolating nuclei as described previously (16,17).…”
Section: For [mentioning
confidence: 99%
“…Previously it has been shown that mimosine functions as an iron chelator (10,35,36). Although chelating iron would increase the expression and activity of HIF-1 and c-Jun/AP-1 transcription factors (30), it also decreases the expression and activity of N-Myc and c-Myc (47,48).…”
Section: Comparison Of the Effects Of Mimosine On Drg-1 Expression Wimentioning
confidence: 99%
See 1 more Smart Citation
“…Among them are p27, an essential regulator of S phase entry; RRM2, a key enzyme supplying converted deoxyribonucleotides for DNA synthesis; and RPA2 functioning in multiple DNA metabolic pathways. [66][67][68] The steady-state levels of these proteins were also not consistently altered in ABCE1-silenced cells (Fig. 6B), implying that translation of at least these few candidates may not be critically dependent on the presence of ABCE1.…”
Section: Discussionmentioning
confidence: 90%
“…In particular, eIF3A is expressed periodically during S phase and may regulate translation of several proteins important for cell cycle control and DNA replication, such as the cyclin-dependent kinase inhibitor p27, ribonucleotide reductase M2 subunit (RRM2) and replication protein RPA2. [65][66][67][68] eIF3A has been previously shown to stimulate RRM2 and to inhibit p27 and RPA2 translation, thus acting in reciprocal directions. [66][67][68] In our study, in both HEK293 and HeLa cells with depleted ABCE1, the expression of none of these proteins was consistently altered as if they were co-regulated by ABCE1 (Fig.…”
Section: Abce1 Downregulation Impairs Cell Proliferation and Cell Cycmentioning
confidence: 99%